Synergistic Interaction of MEK Kinase 2, c-Jun N-Terminal Kinase (JNK) Kinase 2, and JNK1 Results in Efficient and Specific JNK1 Activation - Cheng, Jinke (American Society for Microbiology, 2000)
Mitogen-activated protein kinases (MAPKs) are activated through cascades or modules consisting of a MAPK, a MAPK kinase (MAPKK), and a MAPKK kinase (MAPKKK). Investigating the molecular basis of activation of the c-Jun N-terminal kinase (JNK) subgroup of MAPK by the MAPKKK MEKK2, we found that strong and specific JNK1 activation by MEKK2 was mediated by the MAPKK JNK kinase 2 (JNKK2) rather than by JNKK1 through formation of a tripartite complex consisting of MEKK2, JNKK2, and JNK1. No scaffold protein was required for the MEKK2-JNKK2-JNK1 tripartite-complex formation. Expression of JNK1, JNKK2, and MEKK2 significantly augmented the coprecipitation of, respectively, MEKK2-JNKK2, MEKK2-JNK1, and JNKK2-JNK1, indicating that the interaction of MEKK2, JNKK2, and JNK1 is synergistic. Finally, the JNK1 was activated more efficiently in the MEKK2-JNKK2-JNK1 complex than was the JNK1 excluded from the complex. Thus, formation of a signaling complex through synergistic interaction of a MAPKKK, a MAPKK, and a MAPK molecule like MEKK2-JNKK2-JNK1 is likely to be responsible for the efficient, specific flow of information via MAPK cascades.